Comprehensive review on Plumbago indica: Traditional, pharmacological insights and conservation strategies - Abdulkadir Abdu, Akhilesh Prakash, Rishav Kondal, Sudhir Sharma, Mani Bhagat, Ritu Pal, Hasandeep Singh, Balbir Singh, Sarabjit Kaur (Journal of Applied Pharmaceutical Science, 2024)
Plumbago indica, also known as Indian leadwort or chitrak, is a medicinal plant with a rich history in traditional medicine systems like Ayurveda and Chinese medicine. Its medicinal properties include herbal remedies, powders, and extracts derived from the roots of the plant and leaves, with scientific studies proving its pharmacological capabilities in addressing various medical conditions such as inflammation, oxidative stress, bacterial infections, hepatoprotection, and cancer. The demand for plumbagin in the market has witnessed an upsurge due to the lack of commercial viability in producing the required quantity from the roots of this seedless plant. This review offers a thorough analysis of the morphological traits, growth patterns, and reproductive techniques of this plant. Additionally, in this study, the pharmacological significance, trade market demand, toxicity issues, threat, conservation status, and suggestions for sustainable cultivation methods are also covered. To ensure its continuous availability, it also discusses conservation efforts and its potential for novel drugs.
Keywords: Plumbago indica, Plumbagin, phytochemistry, medicinal uses,conservation